Application of nanotechnology in agricultural sustainability: Absorption, translocation, and challenges of nanoparticles - Yanping Meng; Yingying Feng; Xin Bai; Qinghui Yu; Jiyang Zhou; Juan Wang (Current Plant Biology)
The global agricultural sector has seen significant expansion in recent years, which has raised concerns about food supply, the safety of fertilizers, and the use of genetically modified crops. The growing demand for food, coupled with various environmental issues, has highlighted the importance of adopting sustainable agricultural practices. Recent advancements in the field of nanotechnology suggest that it has the potential to greatly enhance agricultural sustainability, particularly in areas such as fertilizer application, genetic modification, and pest control. The effectiveness of nanomaterials in plants is heavily dependent on the plants' ability to absorb and translocate these nanoparticles. To maximize the efficiency of nanomaterials in the fields of agriculture and plant breeding, this article delves into several key aspects: the influence of the physical and chemical properties of nanoparticles on their translocation within the plant body, the impact of plant structural features on nanoparticle penetration and translocation, and the various ways in which nanoparticles are exposed within different plant species. Understanding these factors is crucial for researchers to gain a more comprehensive insight into how nanoparticles can overcome barriers within plant tissues and cells. It also sheds light on the primary factors that may restrict the effective delivery of nanoparticles. By addressing these challenges, the article aims to enhance the utilization efficiency of nanomaterials in the agricultural sector. This knowledge can facilitate the effective application of nanoparticles across various agricultural domains and foster the sustainable development of both nanotechnology and agriculture as a whole.